A calculus problem by Rocco Dalto

Calculus Level 5

If y 1 ( x ) y_{1}(x) and y 2 ( x ) y_{2}(x) are linear independent solutions to the differential d 2 y d x 2 1 x ( x + 1 ) d y d x + x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 y = 0 \dfrac{d^2y}{dx^2} - \dfrac{1}{x(x + 1)} \dfrac{dy}{dx} + \dfrac{x^2}{(x + 1)^2 (x - \ln(x + 1))^2} y = 0 with initial conditions y 1 ( a ) = 1 , y 1 ( a ) = a 2 ( a + 1 ) , y_{1}(a) = 1, \: y_{1}'(a) = \dfrac{a}{2 * (a + 1)}, y 2 ( a ) = 0 , y 2 ( a ) = 3 2 ( a a + 1 ) , y_{2}(a) = 0, \: y_{2}'(a) = \dfrac{\sqrt{3}}{2} * (\dfrac{a}{a + 1}), where a a is a positive solution to ln ( a + 1 ) = a 1. \ln(a + 1) = a - 1.

Evaluate: 0 e 1 y 1 ( x ) 2 + y 2 ( x ) 2 d x \displaystyle \int_{0}^{e - 1} y_1(x)^2 + y_2(x)^2 \, dx .

Express the result to 6 decimal places.

Refer to Hint in previous problem. . .


The answer is 0.476246.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Dec 2, 2016

Using the substitution z = ln ( x ln ( x + 1 ) ) z = \ln(x - \ln(x+1)) yields the differential equation d 2 y d z 2 d y d z + y = 0 \frac{d^2y}{dz^2} - \frac{dy}{dz} + y \; = \; 0 and we note that z = 0 z=0 when x = a x=a . Note that there is only one positive value a a for which ln ( a + 1 ) = a 1 \ln(a+1) = a-1 , and so a a is well-defined. This equation has the solutions e m z e^{mz} where m = 1 2 ± 1 2 i 3 m = \tfrac12 \pm \tfrac12i\sqrt{3} . Thus we obtain linearly independent solutions y 1 ( x ) = e 1 2 z cos ( 1 2 3 z ) = x ln ( x + 1 ) cos ( 1 2 3 ln ( x ln ( x + 1 ) ) ) y 2 ( x ) = e 1 2 z sin ( 1 2 3 z ) = x ln ( x + 1 ) sin ( 1 2 3 ln ( x ln ( x + 1 ) ) ) \begin{array}{rcl} y_1(x) & = & e^{\frac12z} \cos(\tfrac12\sqrt{3}z) \; = \; \sqrt{x - \ln(x+1)}\cos\big(\tfrac12\sqrt{3} \ln(x - \ln(x+1))\big) \\ y_2(x) & = & e^{\frac12z} \sin(\tfrac12\sqrt{3}z) \; = \; \sqrt{x - \ln(x+1)}\sin\big(\tfrac12\sqrt{3} \ln(x-\ln(x+1))\big) \end{array} Since z ( a ) = a a + 1 z'(a) \,=\, \tfrac{a}{a+1} , it is easy to check that y 1 , y 2 y_1,y_2 as given above are the required solutions of the differential equation. But then y 1 ( x ) 2 + y 2 ( x ) 2 = x ln ( x + 1 ) y_1(x)^2 + y_2(x)^2 = x - \ln(x+1) , and so 0 e 1 ( y 1 ( x ) 2 + y 2 ( x ) 2 ) d x = 0 e 1 ( x ln ( x + 1 ) ) d x = 1 2 ( e 2 2 e 1 ) = 0.476246 \int_0^{e-1} \big( y_1(x)^2 + y_2(x)^2\big)\,dx \; = \; \int_0^{e-1} (x - \ln(x+1))\,dx \; = \; \tfrac12(e^2 - 2e -1) \; = \; \boxed{0.476246}

Rocco Dalto
Nov 28, 2016

Prior to solving the differential d 2 y d x 2 1 x ( x + 1 ) d y d x + x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 y = 0 \dfrac{d^2y}{dx^2} - \dfrac{1}{x(x + 1)} \dfrac{dy}{dx} + \dfrac{x^2}{(x + 1)^2 (x - \ln(x + 1))^2} y = 0 ,
I am going to demonstrate how I constructed the differential, and reduced it to a second order differential with constant coefficients. If you reviewed(or proved) the statement(in the Hint ), as well as my second statement which outlines the construction, you will be familiar with what follows.

Let P ( x ) = 1 x ( x + 1 ) = ( 1 x 1 x + 1 ) P(x) = -\dfrac{1}{x (x + 1)} = -(\dfrac{1}{x} - \dfrac{1}{x + 1}) and let the constant j = 2 j = -2 \implies

d Q d x 2 x ( x + 1 ) Q = 2 Q 3 2 \dfrac{dQ}{dx} - \dfrac{2}{x (x + 1)} Q = -2 Q^{\dfrac{3}{2}} \implies

Q 3 2 d Q d x 2 x ( x + 1 ) Q 1 2 = 2. Q^{-\dfrac{3}{2}} \dfrac{dQ}{dx} - \dfrac{2}{x (x + 1)} Q^{-\dfrac{1}{2}} = -2.

Let W = Q 3 2 2 d W d x = Q 3 2 d Q d x W = Q^{-\dfrac{3}{2}} \implies -2 \dfrac{dW}{dx} = Q^{-\dfrac{3}{2}} \dfrac{dQ}{dx} \implies

d W d x + 1 x ( x + 1 ) W = 1 \dfrac{dW}{dx} + \dfrac{1}{x (x + 1)} W = 1 \implies

d d x ( x x + 1 W ) = x x + 1 \dfrac{d}{dx}(\dfrac{x}{x + 1} * W) = \dfrac{x}{x + 1} \implies

x x + 1 W = ( 1 1 x + 1 ) d x + C = x ln ( x + 1 ) + C \dfrac{x}{x + 1} * W = \int (1 - \dfrac{1}{x + 1}) \: dx + C = x - \ln(x + 1) + C \implies

W = ( x + 1 x ) ( x ln ( x + 1 ) ) + ( x + 1 x ) C . W = (\dfrac{x + 1}{x}) (x - \ln(x + 1)) + (\dfrac{x + 1}{x}) * C.

Let C = 0 W = ( x + 1 x ) ( x ln ( x + 1 ) ) C = 0 \implies W = (\dfrac{x + 1}{x}) (x - \ln(x + 1))

W = Q 1 2 Q = x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 W = Q^{-\dfrac{1}{2}} \implies Q = \dfrac{x^2}{(x + 1)^2 (x - \ln(x + 1))^2} \implies

z ( x ) = Q ( x ) d x = ( 1 1 / ( x + 1 ) x ln ( x + 1 ) 2 ) d x = ln ( x l n ( x + 1 ) ) z(x) = \int \sqrt{Q(x)} \: dx = \int (\dfrac{1 - 1/(x + 1)}{x - \ln(x + 1)^2}) \: dx = \ln(x - ln(x + 1))

Now we have constructed our second order differential d 2 y d x 2 1 x ( x + 1 ) d y d x + x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 y = 0 \dfrac{d^2y}{dx^2} - \dfrac{1}{x(x + 1)} \dfrac{dy}{dx} + \dfrac{x^2}{(x + 1)^2 (x - \ln(x + 1))^2} y = 0 and the substitution z = ln ( x l n ( x + 1 ) ) z = \ln(x - ln(x + 1)) will reduce this differential to a second order differential with constant coefficients, since Q + 2 P Q Q 3 2 = 2. \dfrac{Q' + 2PQ}{Q^{3}{2}} = -2.

Now we begin solving the differential d 2 y d x 2 1 x ( x + 1 ) d y d x + x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 y = 0. \dfrac{d^2y}{dx^2} - \dfrac{1}{x(x + 1)} \dfrac{dy}{dx} + \dfrac{x^2}{(x + 1)^2 (x - \ln(x + 1))^2} y = 0.

From above, let z = ln ( x l n ( x + 1 ) ) d y d x = ( x x + 1 ) ( 1 x ln ( x + 1 ) ) d y d z z = \ln(x - ln(x + 1)) \implies \dfrac{dy}{dx} = (\dfrac{x}{x + 1}) (\dfrac{1}{x - \ln(x + 1)}) \dfrac{dy}{dz}

and,

d 2 y d x 2 = d d x ( d y d z ( x x + 1 ) ( 1 x ln ( x + 1 ) ) ) = \dfrac{d^2y}{dx^2} = \dfrac{d}{dx}(\dfrac{dy}{dz} (\dfrac{x}{x + 1}) (\dfrac{1}{x - \ln(x + 1)}) ) =

d y d z ( x ln ( x + 1 ) x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 ) ) + x 2 ( x + 1 ) 2 ( x ln ( x + 1 ) ) 2 d 2 y d z 2 \dfrac{dy}{dz} (\dfrac{x - \ln(x + 1) - x^2}{(x + 1)^2 * (x - \ln(x + 1))^2)}) + \dfrac{x^2}{(x + 1)^2 * (x - \ln(x + 1))^2} \dfrac{d^2y}{dz^2}

Replacing d 2 y d x 2 \dfrac{d^2y}{dx^2} and d y d x \dfrac{dy}{dx} into the above differential we obtain:

d 2 y d z 2 d y d x + y = 0 m 2 m + 1 = 0 m = 1 2 ± 3 2 \dfrac{d^2y}{dz^2} - \dfrac{dy}{dx} + y = 0 \implies m^2 - m + 1 = 0 \implies m = \dfrac{1}{2} \pm \dfrac{\sqrt{3}}{2} \implies

y ( z ) = e z 2 ( c 1 c o s ( 3 2 z ) + c 2 s i n ( 3 2 z ) ) y(z) = e^\dfrac{z}{2} * (c1 * cos(\dfrac{\sqrt{3}}{2} z) + c2 * sin(\dfrac{\sqrt{3}}{2} z))

z = ln ( x l n ( x + 1 ) ) z = \ln(x - ln(x + 1)) \implies

The general solution is: y ( x ) = x ln ( x + 1 ) ( c 1 c o s ( 3 2 ( ln ( x ln ( x + 1 ) ) ) + c 2 s i n ( 3 2 ( ln ( x ln ( x + 1 ) ) ) ) y(x) = \sqrt{x - \ln(x + 1)} * (c1 * cos(\dfrac{\sqrt{3}}{2} * (\ln(x - \ln(x + 1))) + c2 * sin(\dfrac{\sqrt{3}}{2} * (\ln(x - \ln(x + 1))))

\therefore The two linear independent solutions are:

y 1 ( x ) = c 1 x ln ( x + 1 ) c o s ( 3 2 ( ln ( x ln ( x + 1 ) ) ) y1(x) = c1 * \sqrt{x - \ln(x + 1)} * cos(\dfrac{\sqrt{3}}{2} * (\ln(x - \ln(x + 1)))

y 2 ( x ) = c 2 x ln ( x + 1 ) s i n ( 3 2 ( ln ( x ln ( x + 1 ) ) ) y2(x) = c2 * \sqrt{x - \ln(x + 1)} * sin(\dfrac{\sqrt{3}}{2} * (\ln(x - \ln(x + 1)))

Using the initial conditions y 1 ( a ) = 1 , y 1 ( a ) = a 2 ( a + 1 ) , y_{1}(a) = 1, \: y_{1}'(a) = \dfrac{a}{2 * (a + 1)}, y 2 ( a ) = 0 , y 2 ( a ) = 3 2 ( a a + 1 ) c 1 = c 2 = 1. y_{2}(a) = 0, \: y_{2}'(a) = \dfrac{\sqrt{3}}{2} * (\dfrac{a}{a + 1}) \implies c1 = c2 = 1.

y 1 ( x ) y1(x) and y 2 ( x ) y2(x) are clearly linear independent since y 2 y 1 = t a n ( 3 2 ( ln ( x ln ( x + 1 ) ) ) \dfrac{y2}{y1} = tan(\dfrac{\sqrt{3}}{2} * (\ln(x - \ln(x + 1))) \not= constant.

and,

0 e 1 y 1 ( x ) 2 + y 2 ( x ) 2 d x = 0 e 1 ( x ln ( x + 1 ) ) d x \int_{0}^{e - 1} y1(x)^2 + y2(x)^2 \: dx = \int_{0}^{e - 1} (x - \ln(x + 1)) \: dx

For ln ( x + 1 ) d x \int \ln(x + 1) \: dx

Let u = ln ( x + 1 ) , d v = d x d u = 1 x + 1 u = \ln(x + 1), dv = dx \implies du = \dfrac{1}{x + 1} and v = x v = x \implies

ln ( x + 1 ) d x = x ln ( x + 1 ) ( 1 1 x + 1 ) d x = x ln ( x + 1 ) x + ln ( x + 1 ) = \int \ln(x + 1) \: dx = x \ln(x + 1) - \int (1 - \dfrac{1}{x + 1}) \:dx = x * \ln(x + 1) - x + \ln(x + 1) = ( x + 1 ) ln ( x + 1 ) x (x + 1) * \ln(x +1) - x

\implies

0 e 1 ( x ln ( x + 1 ) ) d x = 1 2 ( x ) ( x + 2 ) ( x + 1 ) ln ( x + 1 ) 0 e 1 = e 2 2 e 1 2 = . 476246 \int_{0}^{e - 1} (x - \ln(x + 1)) \: dx = \dfrac{1}{2} (x) (x + 2) - (x + 1) * \ln(x + 1)|_{0}^{e - 1} = \dfrac{e^2 - 2 e - 1}{2} = .476246 to six decimal places.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...